Optimization of enzymatic production of fatty hydrazides and their application as polyurethane chain extender - Tuan Ismail, Tuan Noor Maznee (2012)
Enzymatic synthesis of fatty hydrazides from palm oil was first carried out using the reaction conditions reported by Mohamad et al. (2008) as for the starting point in optimization work. Fatty hydrazides were prepared by reacting refined, bleached and deodorized (RBD) palm olein with hydrazine monohydrate in the presence of enzyme and n-hexane. As for optimization, response surface methodology of central composite design of quadratic model has been applied. The optimum reaction conditions obtained using pH 7 adjusted hydrazine monohydrate were as follows: temperature, 40oC; time, 18 h; percentage of enzyme, 6% and stirring speed, 350 rpm. Study on the effect of pH of hydrazine monohydrate on the formation of fatty hydrazides indicated that the reaction was best carried out at pH 12. Further study using the optimum reaction conditions established through response surface methodology and hydrazine monohydrate of pH 12 drastically improved the conversion of the fatty hydrazides from 43.8% (pH 7) to 87.5% (pH 12). Composition of the hydrazides analyzed using GC also increased tremendously from 15.77% to 91.87%. A bigger scale production of fatty hydrazides (using 1 kg RBD palm olein instead of 100 g) was conducted using the newly established optimum reaction conditions. However, due to the limitation of the reactor, the reaction mixture could only be stirred at the stirring speed of 150 rpm. But interestingly, the yield of fatty hydrazides produced was further increased by 24.4% and the composition of hydrazides shown by GC chromatogram increased by 6% compared to the hydrazides obtained from 100 g RBD palm olein. The GC/MS analysis indicated that the fatty hydrazides prepared contained a mixture of palmityl hydrazide and oleyl hydrazide. 1H and 13C NMR chromatogram further confirmed the component of fatty hydrazides by the presence of proton chemical resonances, 1H NMR, (600 MHz, DMSO-d6) at δ 8.90 (s, -CONH), 5.32 (m, -CH=CH-), 2.17 (t, J=7.8 Hz,-CH2-CO-), 2.08 (m, -NH2), 1.98 (m, -CH2-CH=CH-CH2-, 4H), 1.46 (m, -CH2CH2CO-), 1.26 (m, -CH2-, 24H), 0.85 (t, -CH3) and carbon chemical resonances, 13C NMR,(150 MHz, DMSO-d6) at δ 171.6 (-CON-) and 129.6 (-CH=CH-). These optimized conditions were then applied for synthesis of fatty hydrazides from other triglycerides such as glyceryl trioleate, soybean oil and glyceryl tristearate. Compositions of fatty hydrazides obtained as shown by GC chromatogram were in the range of 81 to 91%. GC/MS analysis also indicated that glyceryl trioleate-based hydrazides or oleyl fatty hydrazides and soybean fatty hydrazides contained a mixture of palmityl hydrazide, oleyl hydrazide and linoleyl hydrazide. Stearyl fatty hydrazides were not analyzed using GC/MS due to the limitation of the oven temperature of the instrument. 1H and 13C NMR chromatogram further confirmed the component of fatty hydrazides by the presence of proton chemical resonances, 1H NMR, (600 MHz, DMSO-d6) at δ 8.90 (s, -CONH), 5.32 (m, -CH=CH-), 2.17 (t, J=7.8 Hz,-CH2-CO-), 2.08 (m, -NH2), 1.98 (m, -CH2-CH=CH-CH2-, 4H), 1.46 (m, - CH2CH2CO-), 1.26 (m, -CH2-, 24H), 0.85 (t, -CH3) and carbon chemical resonances, 13C NMR, (150 MHz, DMSO-d6) at δ 171.6 (-CON-) and 129.6 (- CH=CH-). Finally, potential application of fatty hydrazides as a chain extender in rigid polyurethane foam was investigated. The reactivity of foaming process for foam and its thermal conductivity value increased with the presence of fatty hydrazides. However, the closed cell content of the foam seemed to decrease, therefore, the rigid polyurethane foam containing fatty hydrazides exhibits slightly inferior insulation property compared to the foam without atty hydrazides. Based on these observations, fatty hydrazides might be more useful to be incorporated in formulation for flexible foam.